Does Participatory Planning Promise Too Much? Global Discourses and the Glass Ceiling of Participation in Urban Malawi. (15th March 2019) - Refstie, Hilde; Millstein, Marianne
ABSTRACT: This article discusses how global ideas on co-production and citizenship built from below are translated into community mobilization and participatory planning practices in urban Malawi. It shows how limited national and local resources, disconnections from national and urban policies of redistribution, and a local politics shaped by both clientelism and democratic reforms create a glass ceiling for what global models of community mobilization and participation are able to achieve. It calls for a more systematic and empirically diverse research agenda to better understand how participatory discourses and practices embedded in grassroots organizing are transferred and mediated in place.